2012
DOI: 10.2337/db11-1065
|View full text |Cite
|
Sign up to set email alerts
|

Morbidly Obese Human Subjects Have Increased Peripheral Blood CD4+ T Cells With Skewing Toward a Treg- and Th2-Dominated Phenotype

Abstract: Obesity is associated with local T-cell abnormalities in adipose tissue. Systemic obesity-related abnormalities in the peripheral blood T-cell compartment are not well defined. In this study, we investigated the peripheral blood T-cell compartment of morbidly obese and lean subjects. We determined all major T-cell subpopulations via six-color flow cytometry, including CD8+ and CD4+ T cells, CD4+ T-helper (Th) subpopulations, and natural CD4+CD25+FoxP3+ T-regulatory (Treg) cells. Moreover, molecular analyses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
94
5
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 52 publications
24
94
5
10
Order By: Relevance
“…Although existing data support the hypothesis that CD8 + cells are the predominant T cell subset in the visceral WAT of obese humans and mice [31,33,45], CD4 + T cells may also regulate insulin sensitivity and adiposity [32]. In line with this, an increased number of activated CD4 + cells has been identified in morbidly obese humans [78]. Second, the mode of action of activated T cells, independent of their CD4 + or CD8 + identity, seems to be through the induction of proinflammatory cytokines, such as TNF-α, IFN-γ, and chemokines, such as CCL2.…”
Section: Conclusion and Future Outlooksupporting
confidence: 51%
“…Although existing data support the hypothesis that CD8 + cells are the predominant T cell subset in the visceral WAT of obese humans and mice [31,33,45], CD4 + T cells may also regulate insulin sensitivity and adiposity [32]. In line with this, an increased number of activated CD4 + cells has been identified in morbidly obese humans [78]. Second, the mode of action of activated T cells, independent of their CD4 + or CD8 + identity, seems to be through the induction of proinflammatory cytokines, such as TNF-α, IFN-γ, and chemokines, such as CCL2.…”
Section: Conclusion and Future Outlooksupporting
confidence: 51%
“…Although the T-reg population correlated positively with TNF-α and glycerol secretion, we could not confirm this finding by quantification of FOXP3 expression in the CD4 + T cell fraction (data not shown). In a previous human study, T-reg cells were found to be increased in the peripheral blood of morbidly obese patients, although no correlation with insulin resistance was observed [39]. Clearly the role of this important cell population in type 2 diabetes needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The impact of obesity on the cells of the adaptive immune system has also been reported. 17 DCs are the bridge between innate and adaptive immune responses. They are responsible for activation and polarisation of T cells, providing multiple signals that shape the adaptive immune response.…”
Section: Discussionmentioning
confidence: 99%